Coupling of knowledge and data in TESOR system - Bao, Ho Tu; Anh, Dao Nam (Journal of Computer Science and Cybernetics, 2016)
In this paper we shall be concerned with the integration of knowledge and data in TESOR system. In particular, TESOR system, an evolutionary for  building knowledge based systems is first introduced. Next, the archilectural paradigm of the integration and  the extension of  the TESOR knowledge representation language for this purpose is given. Finally, the implementation and an application of this coupling system are addressed.